Ca and K decorated germanene as hydrogen storage: An ab initio study. (1st March 2018) - Rojas, Kurt Irvin M.; Villagracia, Al Rey C.; Moreno, Joaquin Lorenzo; David, Melanie; Arboleda, Nelson B.
Abstract: The hydrogen storage capacity and performance of Ca and K decorated germanene were studied using density functional theory calculation. The Ca and K adatoms were found to be sufficiently bonded to the germanene without clustering at the hollow site. Further investigation has shown an ionic bonding is apparent based on the charge density difference and Bader charge analysis. Upon adsorption of H2 on the decorated germanene, it was found that the Ca and K decorated systems could adsorb 8 and 9 H2 molecules, respectively. The adsorption energies of H2 molecules were within the Van der Waals energy (400–435 meV), suggesting weak physisorption. The charge density profile revealed that the electron of H2 moved toward the adatom decoration without leaving the local region of H2 . This suggests that a dipole-dipole interaction was apparent and consistent with the energy range found. Finally, the gravimetric density obtained from the adsorption of H2 on the decorated germanene shows that this material is a potential for H2 storage media. Highlights: Both Ca and K have successfully ionically bonded with single layer germanene. Electronic structure was altered upon binding of Ca or K on germanene. Van der Waals bonding of H2 on Ca and K decorated germanene was observed. Projected gravimetric density for H2 saturated systems passed target.